The Corona Regulation and the public protest in STUTTGART. A doctrinal study of the exercise of freedom of assembly during COVID-19 - Mateos Durán, Arnulfo Daniel (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2020)
In early 2020 the Covid-19 pandemic took the world by surprise. As the virus spread, several governments decided to deploy different measures to limit the number of infections. Such measures constitute new limiting reasons to some constitutional rights, several of them with a warranty already consolidate through the years. This was the case with the freedom of assembly in the German constitutional order. This right has an important place in the objective value order of the Bonn Basic Law. However, this freedom was limited by statutes aimed at protecting the life and integrity of individuals. This paper will analyze a ruling by the German Federal Constitutional Court, in which the effects of the measures against the Covid-19 on the protection of constitutional rights can be seen.